FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDIT - Rudi Riady (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this research is to analyze whether audit structure, role conflict, role ambiguity, good governance, organizational culture and leadership style have an effect to auditor performance. Subject of thisresearch is auditors whom worked at registered public accountant firm in Jakarta. The sample is selected using purposive sampling method. Data were collected using survei method. Number of questionnaires distributed was 200 coppies, but only 168 questionnaires returned. However, only 107 of returned questionnaires were valid for analyses. The conclusion of this research shows that role conflict, role ambiguity, good governance, and organizational culture have influence to auditor performance. However, audit structure and leadership style do not have influence to auditor performance.